2017
DOI: 10.1371/journal.pone.0169501
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization Using Mannatide as a Novel Adjuvant for an Inactivated Influenza Vaccine and Its Adjuvant Effect Compared with MF59

Abstract: Intranasal vaccination is more potent than parenteral injection for the prevention of influenza. However, because the poor efficiency of antigen uptake across the nasal mucosa is a key issue, immunostimulatory adjuvants are essential for intranasal vaccines. The immunomodulator mannatide or polyactin (PA) has been used for the clinical treatment of impaired immunity in China, but its adjuvant effect on an inactivated trivalent influenza vaccine (ITIV) via intranasal vaccination is unclear. To explore the adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…), and an influenza vaccine containing Escherichia coli heat-labile enterotoxin (LT) was linked to Bell’s palsy ( 9 ). Nevertheless, new promising candidates, such as members of the cyclic-di-nucleotide family among others, are under development ( 10 , 11 ). The cyclic-di-nucleotides are second-messenger molecules in bacteria and archea ( 12 , 13 ) and the innate immune system senses them via STING (stimulator of interferon genes) and DDX41 [DEAD (aspartate-glutamate-alanine-aspartate)-box helicase 41] ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…), and an influenza vaccine containing Escherichia coli heat-labile enterotoxin (LT) was linked to Bell’s palsy ( 9 ). Nevertheless, new promising candidates, such as members of the cyclic-di-nucleotide family among others, are under development ( 10 , 11 ). The cyclic-di-nucleotides are second-messenger molecules in bacteria and archea ( 12 , 13 ) and the innate immune system senses them via STING (stimulator of interferon genes) and DDX41 [DEAD (aspartate-glutamate-alanine-aspartate)-box helicase 41] ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Wang W et al, 13 MT in combination with E75 peptide significantly induced splenocytes to produce IFN‐γ in mice. In the study of Ren ST, 14 MT significantly boosted IFN‐γ production by splenic lymphocytes after vaccine antigen stimulation, indicating that MT could promote the cell‐mediated immune response after intranasal vaccination.…”
Section: Resultsmentioning
confidence: 95%
“…Intranasal vaccination is an attractive route as a needle-free vaccine delivery method. When inactivated influenza vaccines were administered intranasally with an appropriate adjuvant, IgA was induced in the respiratory tract [23]. Several preclinical studies on adjuvant-combined, nasal-inactivated vaccines showed protection against infection of influenza virus [24].…”
Section: Protection Of Influenza Virus On Mucosamentioning
confidence: 99%